Key Lime Growing in the Florida Home Landscape - Jonathan H. Crane (EDIS)
Revised! FC47, a 12-page fact sheet by Jonathan Crane, provides homeowners with an overview of this small bushy citrus fruit tree introduced to the Americas by Spanish and Portuguese explorers in the sixteenth century — description, propagation, fruit production, placement in the landscape, care, pest management, concerns with lawn care, harvest, ripening, and storage, use and nutrition. Includes references. Published by the UF Department of Horticultural Sciences, December 2010.